Negative Transpulmonary Pressure Disrupts Airway Morphogenesis by Suppressing Fgf10 - Stanton, Alice E.; Goodwin, Katharine; Sundarakrishnan, Aswin; Jaslove, Jacob M.; Gleghorn, Jason P.; Pavlovich, Amira L.; Nelson, Celeste M. (Frontiers in Cell and Developmental Biology, 2021)
Mechanical forces are increasingly recognized as important determinants of cell and tissue phenotype and also appear to play a critical role in organ development. During the fetal stages of lung morphogenesis, the pressure of the fluid within the lumen of the airways is higher than that within the chest cavity, resulting in a positive transpulmonary pressure. Several congenital defects decrease or reverse transpulmonary pressure across the developing airways and are associated with a reduced number of branches and a correspondingly underdeveloped lung that is insufficient for gas exchange after birth. The small size of the early pseudoglandular stage lung and its relative inaccessibility in utero have precluded experimental investigation of the effects of transpulmonary pressure on early branching morphogenesis. Here, we present a simple culture model to explore the effects of negative transpulmonary pressure on development of the embryonic airways. We found that negative transpulmonary pressure decreases branching, and that it does so in part by altering the expression of fibroblast growth factor 10 (Fgf10). The morphogenesis of lungs maintained under negative transpulmonary pressure can be rescued by supplementing the culture medium with exogenous FGF10. These data suggest that Fgf10 expression is regulated by mechanical stress in the developing airways. Understanding the mechanical signaling pathways that connect transpulmonary pressure to FGF10 can lead to the establishment of novel non-surgical approaches for ameliorating congenital lung defects.